Belajar Matematika dengan Android - Ritonga, Nur Halimah; Sofiyah, Khotna (LANCAH: Jurnal Inovasi dan Tren, 2024)
This article discusses learning mathematics using Android applications. Learning mathematics is a complicated subject for students. Therefore, there is a need for learning methods that are innovative and appropriate to the times, such as technology-based learning. Android applications can be used as an alternative mathematics learning method because of their ease of access and use. Android applications can present mathematics learning material interactively in the form of text, graphics, images, animations and simulations. Students can study material anytime and anywhere independently using a smartphone. This article will explain further the benefits of learning mathematics using Android applications for students and the challenges they face. The aim of this research is to determine the benefits of learning mathematics using Android applications for students and the challenges faced in learning mathematics using Android applications. It is hoped that this research can provide an overview of the potential of Android applications as an alternative mathematics learning method that is innovative and appropriate to the times.